Nature versus nurture: relic nature and environment of the most massive passive galaxies at z < 0.5 : letter to the editor - Tortora, Crescenzo; Napolitano, Nicola R.; Radovich, Mario; Spiniello, C.; Hunt, L.; Roy, N.; Moscardini, Lauro; Scognamiglio, D.; Spavone, M.; Brescia, M.; Cavuoti, S.; D'Ago, G.; et al. (Astronomy and astrophysics, 2020)
Relic galaxies are thought to be the progenitors of high-redshift red - nuggets that for some reason missed the channels of size growth and - evolved passively and undisturbed since the first star formation burst - (at z > 2). These local ultracompact old galaxies are unique - laboratories for studying the star formation processes at high redshift - and thus the early stage of galaxy formation scenarios. - Counterintuitively, theoretical and observational studies indicate that - relics are more common in denser environments, where merging events - predominate. To verify this scenario, we compared the number counts of a - sample of ultracompact massive galaxies (UCMGS) selected within the - third data release of the Kilo Degree Survey, that is, systems with - sizes Re < 1.5 kpc and stellar masses M⋆ - > 8 × 1010 M⊙, with the number counts - of galaxies with the same masses but normal sizes in field and cluster - environments. Based on their optical and near-infrared colors, these - UCMGS are likely to be mainly old, and hence representative of the relic - population. We find that both UCMGS and normal-size galaxies are more - abundant in clusters and their relative fraction depends only mildly on - the global environment, with denser environments penalizing the survival - of relics. Hence, UCMGS (and likely relics overall) are not special - because of the environment effect on their nurture, but rather they are - just a product of the stochasticity of the merging processes regardless - of the global environment in which they live.